2004
DOI: 10.1161/01.atv.zhq0504.0173
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Is Associated With Arterial Stiffness in Apparently Healthy Individuals

Abstract: Objective-C-reactive protein (CRP) levels predict outcome in healthy individuals and patients with atherosclerosis.Arterial stiffness also independently predicts all-cause and cardiovascular mortality and may be involved in the process of atherosclerosis. The aim of this study was to investigate the relationship between stiffness and inflammation in a cohort of healthy individuals. Methods and Results-Pulse wave velocity (PWV) and blood pressure were assessed in 427 individuals. Subjects with cardiovascular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
149
8
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(178 citation statements)
references
References 70 publications
12
149
8
9
Order By: Relevance
“…In healthy individuals, after controlling for age and heart rate, both aortic and brachial PWV were associated with an elevation of the hs-CRP, while AIx was contrarily not elevated 43 . Some studies identified hs-CRP as an independent predictor of cardiovascular events, hypertension, and diabetes 44 .…”
Section: C-reactive Proteinmentioning
confidence: 87%
“…In healthy individuals, after controlling for age and heart rate, both aortic and brachial PWV were associated with an elevation of the hs-CRP, while AIx was contrarily not elevated 43 . Some studies identified hs-CRP as an independent predictor of cardiovascular events, hypertension, and diabetes 44 .…”
Section: C-reactive Proteinmentioning
confidence: 87%
“…Notwithstanding this controversy, CRP remains an important marker to include when investigating CVD development. Various studies report an association between CRP and PWV [10,[36][37][38] but in some, these associations disappear after adjustment for conventional risk factors for CVD [37,39,40]. There are also studies that have reported no association between CRP and PWV [41,42], and it is possible that CRP does not have a causal role in the development of arterial stiffness but may only act as a marker of vascular damage [43].…”
Section: Discussionmentioning
confidence: 99%
“…On the cardiovascular side, both of these markers were also shown to play a role in endothelial dysfunction [9] and arterial stiffening [10,11]. With arterial stiffness being one of the risk factors for CVD [12][13][14][15], it can be asserted that one of the possible mechanisms linking reduced lung function and CVD may be chronic low-grade inflammation leading to arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…in vessel wall stiffening, development of atherosclerotic plaques, etc. (Ross 1993;Pasceri et al 2000;Booth et al 2004;McEniery et al 2004;Duprez et al 2005).…”
Section: The Endotheliummentioning
confidence: 99%